2019
DOI: 10.7759/cureus.4604
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Rowell Syndrome with Lupus Nephritis and Lobar Pneumonia in a Male Child Reported in Pakistan

Abstract: Rowell syndrome (RS) is a rare entity that presents with lupus erythematosus (LE), erythema multiforme (EM) like lesions and characteristic immunological findings including positive rheumatoid factor (RF), speckled antinuclear antibody (ANA) and positive anti-Ro or anti-La antibodies in the serum. Only a few cases have been reported in the literature, mostly in middle-aged women. Our case is about an 11-year-old male child who had a history of pustular rashes over the whole body with scattered targetoid lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…3 The majority of the reported cases showed a satisfactory response to corticosteroids with azathioprine, antimalarial drugs such as chloroquine or hydroxychloroquine, dapsone, or cyclosporine. 1,11,13 Studies have shown that Belimumab, a human monoclonal antibody directed against the B lymphocyte stimulator, is often considered effective in recalcitrant cases of SLE, although data regarding its use in cutaneous SLE is limited. 1 The response to treatment can be assessed using the levels of certain au-dsDNA, anti-Nucl, anti-His, and anti-C1q), among which anti-dsDNA performs the best when assessing disease activity, as suggested by the researchers Shang et al 3 Our patient was subsequently managed with hydroxychloroquine (200 mg once daily), prednisolone (1 mg/kg/day), steroid ointment, a proton pump inhibitor, and sunscreen cream after the diagnosis.…”
Section: Case Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The majority of the reported cases showed a satisfactory response to corticosteroids with azathioprine, antimalarial drugs such as chloroquine or hydroxychloroquine, dapsone, or cyclosporine. 1,11,13 Studies have shown that Belimumab, a human monoclonal antibody directed against the B lymphocyte stimulator, is often considered effective in recalcitrant cases of SLE, although data regarding its use in cutaneous SLE is limited. 1 The response to treatment can be assessed using the levels of certain au-dsDNA, anti-Nucl, anti-His, and anti-C1q), among which anti-dsDNA performs the best when assessing disease activity, as suggested by the researchers Shang et al 3 Our patient was subsequently managed with hydroxychloroquine (200 mg once daily), prednisolone (1 mg/kg/day), steroid ointment, a proton pump inhibitor, and sunscreen cream after the diagnosis.…”
Section: Case Discussionmentioning
confidence: 99%
“…However, the diagnosis becomes challenging when DLE coexists with SLE 3 . The majority of the reported cases showed a satisfactory response to corticosteroids with azathioprine, antimalarial drugs such as chloroquine or hydroxychloroquine, dapsone, or cyclosporine 1,11,13 . Studies have shown that Belimumab, a human monoclonal antibody directed against the B lymphocyte stimulator, is often considered effective in recalcitrant cases of SLE, although data regarding its use in cutaneous SLE is limited 1 .…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Interestingly, many patients reported in the literature are from India. 515 Unlike adults, pediatric patients with RS had a higher frequency of SLE, which may suggest that RS is part of a more serious disease in this population. 515…”
Section: Discussionmentioning
confidence: 99%
“…MAS is increasingly recognized as a feared complication of autoimmune diseases; 7 this has led to the adaptation of the diagnostic criteria for hemophagocytic syndrome published by the Histiocyte Society in 2004, seeking to achieve an earlier diagnosis of MAS in SLE, systemic juvenile idiopathic arthritis, Kawasaki disease, and lymphoma. 8,1618 A validated score has been developed to diagnose reactive HLH termed HScore. 19 Parodi et al.…”
Section: Discussionmentioning
confidence: 99%